Single versus double tendon transfer for improving shoulder function in brachial plexus birth palsy: a meta-analysis of comparative studies - Ahmed O. Sabry; Mohamed K. A. Genedy; Yara Kassem; Marwa El-Difrawy; Reem Shalata; Maziad Hennidi; Farah A. R. Salama; Badr Ali Mohammed Badr; Mohamed Abdel-Wahed (BMC Musculoskeletal Disorders)
Abstract Background Obstetric brachial plexus palsy (OBPP) may result in lifelong shoulder dysfunction despite nerve repair surgery. Tendon transfer has emerged as a surgical option to restore external rotation and abduction in OBPP sequelae. Single and double tendon transfer techniques have been developed, but the optimal approach remains debated. This meta-analysis is the first to compare the range of motion outcomes and complications, particularly loss of midline function (LOM), between the two techniques in managing OBPP sequelae. Methods On January 2025, systematic literature search was performed in five databases (PubMed, Cochrane Library, Embase, Scopus and Web of Science), to identify studies comparing single and double tendon transfer in children with OBPP. Eligible studies underwent quality assessment via MINORS criteria and a meta-analysis using RevMan was conducted to compare the functional outcomes and complications. Results Five retrospective studies encompassing 189 patients were analyzed. The pooled mean difference (MD) in the total modified Mallet score between groups was statistically insignificant (MD = 0.09; 95% CI= -0.68 to 0.85; p > 0.05). Analyses for the sub-scores revealed no differences across all sub-scores. However, for Latissimus Dorsi (LD) single transfers, Abdel-Ghani et al. reported 7.7-fold greater odds of LOM (OR = 0.13; 95% CI = 0.04–0.42; p < 0.05), whereas the pooled LOM of Teres Major (TM) single transfers were not significantly different (OR = 0.40; 95% CI = 0.11–1.47; p > 0.05). Conclusion In conclusion, our meta-analysis suggests that both single and double tendon transfers achieve comparable functional outcomes. However, the data suggests that LD single tendon transfer potentially lowers rate of LOM, though further research is needed to confirm this finding. Clinical trial number Not applicable.